IMPORTANCE OF PROTEATIC ENZYMES IN FERMENTED MEAT PRODUCTS - Meltem SERDAROĞLU; Sumru TÖMEK (Pamukkale University Journal of Engineering Sciences, 1995)
The formation of aroma and taste in fermented sausages is based on proteolytic breakdown. Proteolysis during fermentation and ripening is reflected in an increase in non-protein nitrogen compounds. The fermenting sausage provides optimal conditions for proteolytic enzymes. Muscle proteinases are mainly active during initial fermentation, involuing degradation of myosin and actin, bacterial proteases are more important during the drying period. Added proteolytic enzymes to fermented meat products for increasing proteolysis involves to shorten the ripening period and decreases the costs of storing. Also, organoleptically, fermented meats manufactured with proteinases could yield unique sensory characteristics.